Impact of Sarcopenia on Functional and Oncological Outcomes After Radical Prostatectomy - Angerer, Markus; Salomon, Georg; Beyersdorff, Dirk; Fisch, Margit; Graefen, Markus; Rosenbaum, Clemens M. (Frontiers in Surgery, 2021)
Introduction and Objectives: Knowledge about the significance of sarcopenia (muscle loss) in prostate cancer (PCa) patients is limited. The aim of this study was to determine the influence of skeletal muscle index (SMI) on early functional and pathological outcome in patients undergoing radical prostatectomy (RP). Materials and Methods: One hundred randomly chosen patients who received RP between November 2016 and April 2017 at Martini-Klinik (Hamburg, Germany) were retrospectively assessed. SMI (skeletal muscle mass cross-sectional area at L3/m2) was measured by preoperative staging computed tomography scans at L3 level. Cox regression analysis was applied to determine the impact of SMI on post-operative outcome. Follow-up was 12 months. Continence was defined as no more than one safety pad per day. Results: Mean age of the cohort was 63.6 years. Mean SMI was 54.06 cm2/m2 (range, 40.65–74.58 cm2/m2). Of the patients, 41.4% had pT2, 28.7% had pT3a, and 29.9% had pT3b or pT4 PCa. SMI revealed to be without significant correlation on tumor stage. Follow-up data of 55 patients were available for early functional outcome analysis. SMI showed no significant influence on erectile function in multivariable Cox regression analysis. In multivariable Cox regression analysis, SMI turned out to have no influence on continence rates 6 weeks after surgery. Conclusion: The present study shows that patients undergoing RP have a wide range of SMI. Unlike in other urological malignancies, there was no significant impact of SMI on early functional outcome and pathological outcome. A larger cohort is needed to confirm these results.